Theorizing Contemporary Public Management: International and Comparative Perspectives. (7th August 2013) - Ashworth, Rachel; Ferlie, Ewan; Hammerschmid, Gerhard; Moon, M. Jae; Reay, Trish
Abstract : Ten years ago, the British Journal of Management devoted a special issue to public sector management. The issue identified a series of characteristics associated with public management research, most notably a strong organizational behaviour orientation, a qualitative bent and a predominant healthcare and UK focus. That special issue voiced a 'call to arms' for public management researchers to speak more directly to management research, elucidate a more nuanced account of public management reform, adopt a more explicit theoretical basis and become more internationally comparative. This paper provides a comment on progress against these objectives. We find that public management research has become more diverse, often characterized by an international focus and a wide range of methodological approaches. The paper echoes concerns regarding an increasingly one‐way relationship with general management studies but highlights a more reciprocal connection with organization studies. In doing so, we emphasize three sections of organization scholarship in particular − sociological institutionalism, Foucauldianism and theories of identity. We demonstrate that engagement with these perspectives has improved our understanding of public service reforms and provided opportunities for theoretical contributions beyond the field of public management. The paper concludes with reflections on future public management research.